Research on the Relationship of Consumption Emotion, Experiential Marketing, and Revisit Intention in Cultural Tourism Cities: A Case Study - Chen, Hu; Wang, Yingchao; Li, Na (Frontiers in Psychology, 2022)
Experience marketing plays an important role in improving the quality and upgrading tourism services in cultural tourism cities and helps guide the planning and development, commodity design, and business management of cultural tourism products. However, the urgent problems that need to be solved are as follows: How does experiential marketing in cultural tourism cities affect tourists' consumption behavior? How to adjust consumption emotion in tourist experience and revisit intention? Starting from the experience needs of tourists, this study selected Jinan city, represented by “Qilu culture,” as the research object; discussed the relationship between experiential marketing, consumption emotion, and revisit intention; and used a structural equation model to verify the relationship between the three. This study divided the perception of experiential marketing into four dimensions—sensory experience, action experience, emotional experience, and thinking experience, and divided tourists' revisit intention into two dimensions— “revisit” and “recommendation”. Totally, 305 tourists were randomly selected to participate in the questionnaire survey, and they came from 34 provinces in China. The results showed that cultural tourism cities can enhance tourists' positive consumption emotion through experiential marketing over time, and high-quality tourist consumption experience directly motivates tourists to revisit intention and then promotes tourists to go to cultural tourism cities for secondary consumption. These results suggest that cultural tourism cities should start from Maslow's hierarchy of needs theory, pay attention to the needs of tourists at different levels, and adopt effective experiential marketing strategies from tourism experience to improve the quality of tourists' travel experience and promote tourists' revisit intention.